Review on Krzysztof Pietkiewicz. Paleografia Ruska. – Warszawa : Wydawnictwo DiG, 2015. – 612 c. - Черний, Дмитро (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
Review on Krzysztof Pietkiewicz. Paleografia Ruska. – Warszawa : Wydawnictwo DiG, 2015. – 612 c.